Redefining Business Model in Post Covid-19 - Juhary, Ali (2020)
Professor Dr Juhary Ali, the Dean of School of Management, AeU, as the Invited Speaker, in the International Conference on Environmental and Technology of Law, Business and Education: Post COVID 19- 2020 on 26 September 2020.